2007
DOI: 10.1007/s11293-007-9089-3
|View full text |Cite
|
Sign up to set email alerts
|

The Electoral College System, Political Party Dominance, and Voter Turnout, With Evidence from the 2004 Presidential Election

Abstract: Voter turnout, Political party dominance, Electoral college, D72,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Moreover, robustness testing affirms the strength and consistency of these findings. Interestingly, the female labor force participation rate has been used as a control variable in three prior studies (Verba et al 1997;Cebula 2004;Cebula and Meads 2008). In the first of these studies (Verba et al 1997), which involved data for the 1992 election cycle, female labor force participation was not found to significantly raise aggregate voter turnout (or women's engagement in political activities).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, robustness testing affirms the strength and consistency of these findings. Interestingly, the female labor force participation rate has been used as a control variable in three prior studies (Verba et al 1997;Cebula 2004;Cebula and Meads 2008). In the first of these studies (Verba et al 1997), which involved data for the 1992 election cycle, female labor force participation was not found to significantly raise aggregate voter turnout (or women's engagement in political activities).…”
Section: Discussionmentioning
confidence: 99%
“…In a time series study of the period 1960, Cebula (2004 found the first difference of the female labor force participation rate to elevate the percentage voter turnout. The third of these studies (Cebula and Meads 2008) uses the female labor force participation rate as a control variable in a cross-section investigation of the impact of the Electoral College and political party dominance on the 2004 general election, finding a positive and statistically impact thereof upon voter turnout. These three studies involved estimations of rudimentary models by Ordinary Least Squares.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent scholarship has increasingly highlighted that economic adversity can also motivate action. County-level (Burden and Wichowsky, 2014) and State-level analyses (Cebula and Toma, 2006; Cebula and Meads, 2008) from the US have documented the positive impact of unemployment on turnout, strongly suggesting that economic hardship does not necessarily lead to depressed participation levels.…”
Section: Major Life Events and The Habit Of Votingmentioning
confidence: 99%